2021
DOI: 10.1002/advs.202001701
|View full text |Cite
|
Sign up to set email alerts
|

HNRNPL Circularizes ARHGAP35 to Produce an Oncogenic Protein

Abstract: Circular RNAs (circRNAs) are an intriguing class of widely prevalent endogenous RNAs, the vast majority of which have not been characterized functionally. Here, we identified a novel oncogenic circRNA originating from the back-splicing of Exon2 and Exon3 of a tumor suppressor gene, ARHGAP35 (also known as P190-A), termed as circARHGAP35. have observe that circARHGAP35 and linear ARHGAP35 have antithetical expression and functions. Interestingly, circARHGAP35 contains a 3867 nt long ORF with an m 6 A-modified s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(84 citation statements)
references
References 53 publications
(64 reference statements)
1
81
0
2
Order By: Relevance
“…Growing evidence has uncovered that circRNAs are frequently deregulated and play vital roles in human cancers ( Fontemaggi et al, 2021 ), including CRC ( Li et al, 2018 ; Li Y. et al, 2021 ; Yu and Lei, 2021 ). Several studies have revealed the regulatory roles of circRNAs in cellular metabolism ( He et al, 2017 ; Li et al, 2019c ; Yu et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidence has uncovered that circRNAs are frequently deregulated and play vital roles in human cancers ( Fontemaggi et al, 2021 ), including CRC ( Li et al, 2018 ; Li Y. et al, 2021 ; Yu and Lei, 2021 ). Several studies have revealed the regulatory roles of circRNAs in cellular metabolism ( He et al, 2017 ; Li et al, 2019c ; Yu et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“… 117 FTO circRNA ARHGAP35 decrease promote translation HCC Li et al. 118 YTHDF2 circRNA recognition suppress immunity mammalian cells Chen et al. 119 YTHDC1 circNSUN2 recognition export to cytoplasm from nucleus CRC Chen et al.…”
Section: Roles Of M 6 a Methylation On Circrnasmentioning
confidence: 99%
“…Overexpression of the m 6 A demethylase FTO significantly reduced the abundance of m 6 A and translation of the oncogenic protein, confirming that m 6 A modification is essential for the efficient protein translation from circARHGAP35. 118 …”
Section: Roles Of M 6 a Methylation On Circrnasmentioning
confidence: 99%
“…Studies found that CircARHGAP35 has a cancer-promoting effect in HCC, whereas the parent gene ARHGAP35 of CircARHGAP35 has a cancer-suppressing effect. Further exploration of the mechanism found that the CircARHGAP35 sequence contains a 3867 nt long ORF sequence spanning the splice junction, which can encode a new protein of 1289aa [ 130 ]. This protein overlaps with the sequence of the ARHGAP35 parent gene protein at the N-terminus and only a short segment at the C-terminus is a unique sequence.…”
Section: Circrna Translation Peptides In Tumorsmentioning
confidence: 99%